DIVIDEND PAYOUT RATIO DAN FAKTOR YANG MEMPENGARUHINYA PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - TITA DEITIANA; STEVEN YAP; ERSANIA ERSANIA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
This study aims to examine the factors that affect the Dividend Payout Ratio in food and beverage companies listed on the Indonesia Stock Exchange for the period 2011-2018. The research method used is purposive sampling in the sample collection technique, there are 7 companies that meet the criteria. In this study, it was analyzed using descriptive statistics and panel data regression methods with a fixed effect model to test the hypothesis. This research is processed using eviews 9 software. The results of this study Return on Asset, Current Ratio, Collateralized Asset do not have an influence on the Dividend Payout Ratio, but Debt To Equity Ratio, Firm Size have an influence on the Dividend Payout Ratio.